Flexural behavior of beam to column joints with or without an overlying concrete slab. (15th November 2019) - Mou, Ben; Zhao, Fei; Qiao, Qiyun; Wang, Lingling; Li, Haitao; He, Baojie; Hao, Zhiyu
Highlights: Four beam-column joints were tested to investigate the composite action. Due to the composite action, there is a possibility of fracture near the connection. The composite action was particularly significant under the sagging moment. Abstract: Composite action between a steel frame and an overlying slab plays an important role in the structure design of a beam-column joint in a steel or composite framed structure. This research investigates the seismic performance of a joint between a steel beam and a hollow square steel (HSS) or a concrete filled square tubular (CFST) column with or without an overlying concrete slab. The objective of this research is to evaluate the composite action between the steel girder and concrete slab. Four T-shaped beam to column joints are tested under cyclic loadings. The main experimental parameters are column type (HSS or CSFT) and concrete slab (with or without). Secondly, the seismic behavior of the joint is investigated in terms of failure mode, hysteretic behavior, skeleton curve, stiffness degradation, and strain distribution. Plastic deformation is concentrated at the beam end and brittle fracture is effectively avoided in the vicinity of the beam-to-column joints. All the tested specimens exhibit excellent energy dissipation capacity and ductility. The composite action between a steel girder and a concrete slab significantly enhance the capacity of the joint in terms of stiffness and yield bending moment. The plastic bending moment capacity is, however, slightly improved.